2012
DOI: 10.1002/cctc.201200550
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Evolution by Carbonaceous Nanoparticle Aggregates that were derived from Cobalt Phthalocyanine

Abstract: On HER majesty′s secret service: A carbonaceous material that was based on pyrolyzed cobalt phthalocyanine showed catalytic activity for the hydrogen‐evolution reaction (HER) in aqueous acidic electrolytes and functioned as a H+‐reduction catalyst in a convenient, safe, all‐solid‐state water electrolyzer by using a perfluorosulfonate ion‐exchange polymer membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…[24][25][26] Quite recently, we developed a Co-containing carbonaceous nanoparticle aggregate by sublimation and pyrolysis of Co phthalocyanine (CoPc), which is a new type of HER catalyst functioning in the cathode of the PEM electrolyzer. [27] Highly stable catalytic activity was observed in a 100 h intermittent operation. However, the activity was much lower than that produced by conventional Pt-based catalysts, leading to a high overpotential and low efficiency of the PEM electrolyzer.The results of a previous study suggested that the active site in the carbonaceous catalyst was the Co atom coordinated by four N atoms and embedded in the carbon matrix (CoÀN 4 moiety), which was derived from the center of CoPc.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…[24][25][26] Quite recently, we developed a Co-containing carbonaceous nanoparticle aggregate by sublimation and pyrolysis of Co phthalocyanine (CoPc), which is a new type of HER catalyst functioning in the cathode of the PEM electrolyzer. [27] Highly stable catalytic activity was observed in a 100 h intermittent operation. However, the activity was much lower than that produced by conventional Pt-based catalysts, leading to a high overpotential and low efficiency of the PEM electrolyzer.The results of a previous study suggested that the active site in the carbonaceous catalyst was the Co atom coordinated by four N atoms and embedded in the carbon matrix (CoÀN 4 moiety), which was derived from the center of CoPc.…”
mentioning
confidence: 93%
“…These surface concentrations decreased over the second heat treatment with an increase in T, but increased with an increase in m. This dependency is in agreement with that observed in a previous study. [27] The Co oxidation states were + II and/or + III, which remained unchanged after the second heat treatment with an increase in T (Figure S1). The N atoms were mainly included in the form of pyridinic and graphitic N atoms ( Figure S2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It's not produce greenhouse gases and other harmful chemical compounds after 33 burning. 12,13 40 An advanced catalyst for the electrochemical hydrogen evolution reaction (HER) 41 should reduce the over-potential and consequently increases the efficiency of this important 6 mixture was then filtered and washed with 5.0 wt% HCl aqueous solution and repeatedly 125 was washed with deionized water until the pH of the filtrate became neutral. 7-9 Water splitting is 34 one of the helpful methods to generate H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Phthalocyanines (Pcs) and metallophthalocyanines (MtPcs) have recently received considerable attention due to their unique properties, such as high thermal and chemical stability, excellent photoconductivity, intense optical absorptions in visible–near infrared optical region, and the well‐defined coupling of the electronic π‐systems . Because of these special properties, Pcs and MtPcs have been widely studied as photosensitizer in solar energy conversion, photodynamic therapy, catalysts, information storage, optically active self‐assembly, and so on . However, the poor solubility and slippery π–π stacks limited their applications.…”
Section: Introductionmentioning
confidence: 99%